(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Conveying system plays an important role in various industries to convey the material from one end to other end. The purpose of the conveying system is to reduce the human effort and save time with the use of new innovative technology such that it also minimizes the accidents cases in industries. Among all conveying systems, belt conveyor is the most suitable conveying system used by most of the industries across the world, whether it is power industry, chemical industry petroleum industry etc. and many more. The main application of the conveyor belt can be seen in the industries where material have to be conveyed for long distance in such case it plays a vital role to full fill the requirement. As per the construction, the belt is main part of belt conveyor as it is the only part of the whole system that travels throughout the conveyor carrying the material above it. The construction of the belt mainly consists of the rubber with carcass material inside which provides the strength to the belt. This thesis presented the significance of the carcass material and analytical analysis performed to analyse the stress and deformation on the belt conveyor using various layering materials such as carcass, pineapple fibre and banana fibre. The CAD model is created using CAD software CATIA V5 and the finite element analysis performed on the belt using the software ANSYS 19.